The emotional intelligence 2.0 - Bradberry, Travis; Greaves, Jean. (Sna Diego, CA : TalentSmart, 2009)
Presents techniques for employing emotional intelligence in practical situations at home, at work, and in relationships.
Keywords: Emotional intelligence